2004
DOI: 10.1073/pnas.0406075101
|View full text |Cite
|
Sign up to set email alerts
|

Differential nitros(yl)ation of blood and tissue constituents during glyceryl trinitrate biotransformation in vivo

Abstract: Nitric oxide (NO)-derived products may modify tissue constituents, forming S-and N-nitroso adducts and metal nitrosyls implicated in NO signaling. Nitrovasodilator drugs have been in widespread use for more than a century, yet their biotransformation pathways to NO and their effects as NO donors across tissues remain ill defined. By using a metabonomics approach (termed ''NObonomics'') for detailing the global NO-related metabolism of the cornerstone nitrovasodilator, glyceryl trinitrate (GTN; 0.1-100 mg͞kg), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 49 publications
2
56
1
Order By: Relevance
“…Since glutathione is the most abundant cellular thiol (15-30 nmol/mg protein), formation of GSNO is expected to parallel the activity of NOS. In fact, several studies have confirmed the formation of GSNO in biological systems (15,18,34).…”
Section: Discussionmentioning
confidence: 81%
“…Since glutathione is the most abundant cellular thiol (15-30 nmol/mg protein), formation of GSNO is expected to parallel the activity of NOS. In fact, several studies have confirmed the formation of GSNO in biological systems (15,18,34).…”
Section: Discussionmentioning
confidence: 81%
“…This method is based on the separation of nitrite and nitrate by ion chromatography, followed by online reaction of nitrate to nitrite, postcolumn derivatization with Griess reagent, and detection at 540 nm. Proteins in each sample were removed by centrifugation at 10,000 g for 5 min following methanol precipitation (jejunum-methanol ϭ 1:2 weight/volume, 4°C) (26).…”
Section: Methodsmentioning
confidence: 99%
“…29 However, the contribution of this or other enzyme systems to the overall vasodilation by these drugs is difficult to assess because multiple metabolic pathways appear to act in concert. 30 In view of the range of organic nitrites and related compounds that act as vasodilators, it is not surprising that potassium and sodium nitrites were tested in this regard. In 1880, Reichert and Mitchell 31 published a very full account of the biological action of potassium nitrite on humans and animals.…”
Section: Nitrite As a Vasodilatormentioning
confidence: 99%